2015
DOI: 10.1111/eip.12253
|View full text |Cite
|
Sign up to set email alerts
|

Domain‐specific impairment in cognitive control among remitted youth with a history of major depression

Abstract: Aim Impairment in neuropsychological functioning is common in major depressive disorder (MDD), but it is not clear to what degree these deficits are related to risk (e.g., trait), scar, burden, or state effects of MDD. The objective of this study was to use neuropsychological measures, with factor scores in verbal fluency, processing speed, attention, set-shifting, and cognitive control in a unique population of young, remitted, un-medicated, early course individuals with a history of MDD in hopes of identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 67 publications
3
48
0
Order By: Relevance
“…This could suggest that the attenuated connectivity within the CCN detected in individuals with rMDD in our study is not simply a result of having a CCN that has different boundaries than those identified in prior studies. Our model of emotion regulation in MDD hypothesizes that some individuals have weaker capacity for cognitive control of emotion even in periods of relative wellness (Peters et al, 2015;Langenecker et al, 2014); although this study did not involve an emotion regulation task, the strength of the CCN at rest was attenuated in rMDD and was associated with cognitive factors involved in maladaptive emotion regulation. A lack of CCN coherence might interfere with the ability to exert top-down control over limbic activity to inhibit perseverative thinking states such as rumination (e.g., De Raedt and Koster, 2010;Joormann, 2010;Phillips et al, 2008;Roberts et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This could suggest that the attenuated connectivity within the CCN detected in individuals with rMDD in our study is not simply a result of having a CCN that has different boundaries than those identified in prior studies. Our model of emotion regulation in MDD hypothesizes that some individuals have weaker capacity for cognitive control of emotion even in periods of relative wellness (Peters et al, 2015;Langenecker et al, 2014); although this study did not involve an emotion regulation task, the strength of the CCN at rest was attenuated in rMDD and was associated with cognitive factors involved in maladaptive emotion regulation. A lack of CCN coherence might interfere with the ability to exert top-down control over limbic activity to inhibit perseverative thinking states such as rumination (e.g., De Raedt and Koster, 2010;Joormann, 2010;Phillips et al, 2008;Roberts et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Consistent with this possibility, one study found attenuated connectivity within the CCN among adolescent girls at high risk due to having a parental history of depression, although this study did not evaluate cognitive vulnerability features (Clasen et al, 2014). Given that aberrant CCN functioning may underlie cognitive factors that are known to confer risk for MDD onset or relapse (e.g., Abela and Hankin, 2011;Alloy et al, 2006;Langenecker et al, 2007aLangenecker et al, , 2014Stange et al, 2014Stange et al, , 2016; for a review, see Alloy et al, 2016), longitudinal clinical staging studies are needed to determine whether deficits in CCN connectivity confer similar risk, may represent an early scar of illness, or a combination thereof (Grierson et al, 2016;Peters et al, 2015). To this end, recent studies have demonstrated that greater CCN task-based activation (including dorsolateral prefrontal cortex and inferior parietal lobule) during inhibitory control predicted a greater likelihood of responding to antidepressant treatment for MDD (Gyurak et al, 2016;Langenecker et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations